Membangun Sistem Text-to-Audiovisual Bahasa Indonesia Berdasarkan Database Suara Berbasis Suku Kata Untuk Mendukung Pembelajaran Pelafalan Bahasa Indonesia - Arifin Arifin; Surya Sumpeno; Mochamad Hariadi; Arry Maulana Syarif (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2018)
This paper aims to develop a system Text-to-Audio Visual Indonesian to support learning of Indonesian pronunciation based on speech database syllable-based. This system can visualize the pronunciation of the sentences Indonesian synchronized with speech signals. We conduct several research stages, namely forming the Indonesian viseme models, creating the speech database syllable-based, converting the text into syllables dan synchronizing. The synchronization process is a compilation the viseme models and the speech signal based on input text. This system was evaluated by involving 30 respondents who rate the system based on “lip-reading”. Each respondent provides an assessment of the 10 Indonesian sentences about the level of compatibility between the visualization of syllable and speech spoken based on text input. The MOS methode (Mean Opinion Score) is used to calculate the average ratings of respondents. MOS calculation results is 4.24, It shows that the level of conformity visualization syllable pronunciation and spoken voice is good.